Renal function decline and impact on vitamin D levels, parathyroid hormone and control of calcemia and phosphataemia (Research, Society and Development, 2022)
This study is descriptive where the initial population was 7,895 patients, being first characterized according to the reference of each exam and classified in below, within and above the reference intervals. Then, those who performed, together, the dosages of vitamin D, creatinine and eGFR were filtered, for which the median, standard deviation, minimum and maximum were calculated, in addition to the classification into six groups, according to KDIGO (Kidney Disease: Improving Global Outcomes), considering the gender variable. For each group, the results of vitamin D were statistically analyzed, in which a significant difference was observed for males with p = 0.032 between G1 and G2 and p = 0.0012 between G1 and G3a, and no significant difference was observed for females . Standard and mean deviations were also calculated for the other tests in order to compare the results between the groups, an increase in the mean of PTH levels was noted as the GFR worsened, that is, G1 = 44.76 pg/mL (±10 .99); G2 = 61.63pg/mL (±24.93); G3a = 62.1 (±43.95); G3b = 65.5 pg/mL (±42.71); G4 = 94.11 pg/mL (±67.97); G5 = 464.5 (±529.63). The results show that there is a renal influence on hormone-mineral metabolism, due to increased PTH levels with the worsening of CKD and fluctuation in vitamin D levels, however many of the evaluated patients have other medical conditions, such as heart disease, diabetes, among others, in addition to the use of medication, or even vitamin D replacement, which can influence the results of the exams.